1998
DOI: 10.1007/s004210050444
|View full text |Cite
|
Sign up to set email alerts
|

Competitive sustained exercise in humans, lymphokine activated killer cell activity, and glutamine ? an intervention study

Abstract: This study examined whether oral glutamine supplementation abolishes some of the exercise-induced changes in lymphocyte functions following long-term intense exercise. A group of 16 marathon runners participating in The Copenhagen Marathon 1996 were placed randomly in either a placebo (n = 7) or a glutamine receiving group (n = 9). Each subject received four doses of either placebo or glutamine (100 mg x kg(-1)) administered at 0, 30, 60, and 90-min post-race. In the placebo group the plasma glutamine concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 32 publications
3
25
0
5
Order By: Relevance
“…It has been postulated that restoring glutamine levels after prolonged exercise to physiological levels may help the immune system to resist infections. Although oral provision of glutamine, or branched chain amino acids as a glutamine precursor, abolishes the post-exercise plasma glutamine decrease, it has no consistent effect on lymphocyte or neutrophil counts (Rohde et al, 1998;Walsh et al, 2000;Peters et al, 2001a;Krzywkowski et al, 2001a), salivary IgA (Krzywkowski et al, 2001b), oxidative burst activity (Walsh et al, 2000), NKCA (Rohde et al, 1998;Walsh et al, 2000) or plasma IL-6 (Castell et al, 1997;Hiscock et al, 2003) after exercise. Although it was suggested that glutamine could enhance Th1-type immune response in swimmers submitted to 4 weeks of intensive training, there was no significant difference in glutamine levels between athletes who developed URT infection and those who did not (Mackinnon and Hooper, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been postulated that restoring glutamine levels after prolonged exercise to physiological levels may help the immune system to resist infections. Although oral provision of glutamine, or branched chain amino acids as a glutamine precursor, abolishes the post-exercise plasma glutamine decrease, it has no consistent effect on lymphocyte or neutrophil counts (Rohde et al, 1998;Walsh et al, 2000;Peters et al, 2001a;Krzywkowski et al, 2001a), salivary IgA (Krzywkowski et al, 2001b), oxidative burst activity (Walsh et al, 2000), NKCA (Rohde et al, 1998;Walsh et al, 2000) or plasma IL-6 (Castell et al, 1997;Hiscock et al, 2003) after exercise. Although it was suggested that glutamine could enhance Th1-type immune response in swimmers submitted to 4 weeks of intensive training, there was no significant difference in glutamine levels between athletes who developed URT infection and those who did not (Mackinnon and Hooper, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Five studies (Nieman et al, 1997b, c;Rohde et al, 1998;Henson et al, 1999;Krzywkowski et al, 2001a) assessed NKCA, expressing it in lytic units or adjusting for NK cell counts. NKCA was affected by the intervention in one study (Henson et al, 1999), where triathletes consumed a 6% CHO beverage.…”
Section: Nutrition and Exercise-induced Immunodepressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rohde et al 68,69) showed glutamine supplementation suppressed the decreases in plasma glutamine levels after cycle ergometer exercise and a marathon run, but the activity of lymphokine-activated killer cells was similar between the glutamine supplementation and placebo groups. These results do not support the hypothesis that decreased plasma glutamine levels contribute, in part, to impaired immune function after exercise.…”
Section: Taurinementioning
confidence: 99%
“…Glutamine supplementation had no effect on a number of cellular parameters, except for a small reduction in exercise-induced neutrocytosis. Rohde et al (1998aRohde et al ( , 1998b in two placebocontrolled intervention studies (16 runners and 8 cyclists, respectively) found no effect of glutamine supplementation on a number of lymphocyte subpopulations and functional parameters. Walsh et al (2000) studied seven well-trained men who performed exercise in what appears to have been a placebo-controlled, crossover study.…”
Section: Immune Health (Id 733)mentioning
confidence: 99%